Incorporating Stakeholder Engagement, Financial Implications and Values in Corporate Social Responsibility: A Proposed Model from an African Context - Aminu Ahmadu Hamidu; Md. Harashid Haron; Azlan Amran (International Journal of Economics and Financial Issues, 2017)
Corporate Social Responsibility in Africa is mainly characterised by the features of socio-economic environment like; poverty, underdevelopment, poor infrastructures, weak governmental functionaries. This makes all the drivers or motivating reasons to be an avenue for addressing issues relating to socio-economic development of communities. The motivating factors for CSR from an African context present a set of reasons to engage in CSR with a view to fulfil obligations to society. Stakeholder engagement insures all stakeholder expectations are in conformity with what managers are ready to offer in terms of CSR initiatives and policies. Studying the financial implications of CSR afford the organisation a basis for making long term plans on CSR because it is only on a long term basis that CSR becomes more profitable and lesser in demerits. Influence of religion/Cultural values is a major aspect having impact on all decision making of managers and CSR is also included. The model proposed at the end of this paper is expected to be more elaborate and applicable towards attaining proper implementation of CSR by introducing necessary steps such as; stakeholder engagement, financial implications and beliefs/cultural values. This paper at the end will answer to this need of having a foundational base to Visser's pyramid model of African CSR before attempting to prioritise between the four dimensions of CSR.